2019
DOI: 10.1177/0272989x19862800
|View full text |Cite
|
Sign up to set email alerts
|

On the Likelihood of Surrogates Conforming to the Substituted Judgment Standard When Making End-of-Life Decisions for Their Partner

Abstract: A considerable proportion of end-of-life decisions are made by the patient’s next-of-kin, who can be asked to follow the substituted judgment standard and decide based on the patient’s wishes. The question of whether these surrogate decision makers are actually able to do so has become an important issue. In this study, we examined how the likelihood of surrogates conforming to the substituted judgment standard varies with individual differences in mortality acceptance and confidence in their decision making. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This is also supported by findings in the medical domain, where people accept less risk for others (Batteux, Ferguson, & Tunney, 2019a;Polman & Wu, 2020). These show that, for others, people are more likely to choose a treatment to avoid a painful or deadly illness (Batteux, Ferguson, & Tunney, 2019c;Garcia-Retamero & Galesic, 2012), while also more likely to refuse a treatment involving a risk of death (Batteux, Ferguson, & Tunney, 2019b).…”
supporting
confidence: 63%
See 3 more Smart Citations
“…This is also supported by findings in the medical domain, where people accept less risk for others (Batteux, Ferguson, & Tunney, 2019a;Polman & Wu, 2020). These show that, for others, people are more likely to choose a treatment to avoid a painful or deadly illness (Batteux, Ferguson, & Tunney, 2019c;Garcia-Retamero & Galesic, 2012), while also more likely to refuse a treatment involving a risk of death (Batteux, Ferguson, & Tunney, 2019b).…”
supporting
confidence: 63%
“…This is also supported by findings in the medical domain, where people accept less risk for others (Batteux et al, 2019a; Polman & Wu, 2020). These show that, for others, people are more likely to choose a treatment to avoid a painful or deadly illness (Batteux et al, 2019c; Garcia-Retamero & Galesic, 2012), while also more likely to refuse a treatment involving a risk of death (Batteux et al, 2019b). On the whole, it seems that people are motivated by avoiding a risk of death to a greater extent for others (Von Gunten & Scherer, 2018), even at the expense of their quality of life (Batteux et al, 2019c).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They all reported feeling they lacked the necessary confidence to make such a decision since no legal documents for care preferences at the end of life had been established by any of the patients. Previous studies have found that early discussions about the end of life among family members could ease the decisionmaking process (Batteux et al, 2019(Batteux et al, , 2020. With such documents in place, relatives and family members tend to gain more confidence in making the right decisions that align with the patient's preferences.…”
Section: Discussionmentioning
confidence: 99%